Implementasi Peraturan Presiden Republik Indonesia Nomor 16 Tahun 2018 Tentang Pengadaan Barang Dan Jasa Pemerintah Pada Unit Pelaksana Teknis Jalan Dan Jembatan Kotanopan Dinas Bina Marga Dan Bina Konstruksi Provinsi Sumatera Utara - Matondang, Andi Hakim; Hartono, Budi; Harahap, Dumasari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to find out and analyze the implementation and constraints in the Presidential Regulation of the Republic of Indonesia No. 16 of 2018 concerning Procurement of Government Goods and Services to the Kotanopan Road and Bridge Technical Implementation Unit of the Highways and Construction Services of North Sumatra Province. This research uses a descriptive method with a qualitative approach which is presented descriptively with a public administration juridical approach. The results showed that the Kotanopan Road and Bridge Technical Implementation Unit of the Highways and Construction Services of North Sumatra Province had not fully implemented the Procurement of Goods and Services (PBJ) according to Presidential Decree No. 16 of 2018. The obstacles faced are: there are individuals who seek personal gain from the implementation of road and bridge projects, the government's budget provision is often late, causing project implementation to falter, it is often difficult to identify the most urgent road and bridge needs due to weak information systems, as well as the lack of cooperation from external partner companies that try to cover up weaknesses in the results of project work at the time of handover.